Dated gene duplications elucidate the evolutionary assembly of eukaryotes - Christopher J. Kay; Anja Spang; Gergely J. Szöllősi; Davide Pisani; Tom A. Williams; Philip C. J. Donoghue (Nature, 2026)
Abstract The origin of eukaryotes was a formative but poorly understood event in the history of life. Current hypotheses of eukaryogenesis differ principally in the timing of mitochondrial endosymbiosis relative to the acquisition of other eukaryote novelties 1 . Discriminating among these hypotheses has been challenging, because there are no living lineages representative of intermediate steps within eukaryogenesis. However, many eukaryotic cell functions are contingent on genes that emerged from duplication events during eukaryogenesis 2,3 . Consequently, the timescale of these duplications can provide insights into the sequence of steps in the evolutionary assembly of the eukaryotic cell. Here we show, using a relaxed molecular clock 4 , that the process of eukaryogenesis spanned the Mesoarchaean to late Palaeoproterozoic eras. Within these constraints, we dated the timing of these gene duplications, revealing that the eukaryotic host cell already had complex cellular features before mitochondrial endosymbiosis, including an elaborated cytoskeleton, membrane trafficking, endomembrane, phagocytotic machinery and a nucleus, all between 3.0 and 2.25 billion years ago, after which mitochondrial endosymbiosis occurred. Our results enable us to reject mitochondrion-early scenarios of eukaryogenesis 5 , instead supporting a complexified-archaean, late-mitochondrion sequence for the assembly of eukaryote characteristics. Our inference of a complex archaeal host cell is compatible with hypotheses on the adaptive benefits of syntrophy 6,7 in oceans that would have remained largely anoxic for more than a billion years 8,9 .